Jan Sobieski jako czytelnik Biblii w świetle Listów do Marysieńki - Pawłowski, Rafał (Tematy i Konteksty, 2016)
To date, studies of Jan Sobieski’s letters have meticulously been setting aside biblical reminiscences, which occur over the entire set of his enormous epistles to his wife. Not entirely seriously, we can say that the fame of military perfection and literary excellence overshadow subtle and occasional references to the Bible. Biblical references uncover for the reader an image of a humble man subordinated to God’s will, who wants to atone for his sins and transgressions in his lifetime. In the power of God he was also looking for relief and answers when his conjugal life was not doing best. Sobieski was also deeply convinced of the immutability of God’s judgments which were always faultless (providentialism).